Integration of Solar Panels and Agriculture through Agrivoltaic Farming in Harapan Farmer Group, Palangka Raya - Suprayogi, Thathit; Arsana, Mu'afa; Fatiqin, Awalul; Hidayat, Nur; Shodri, Muhammad Rifqi; Alfanaar, Rokiy; Rahman, Sudarman; Febrianto, Yahya; Citrariana, Shesanthi (Bulletin of Community Engagement, 2024)
This community service activity aims to increase energy independence and agricultural productivity in the Harapan Farmer Group, Palangka Raya, through the application of solar panel-based agrivoltaic farming technology. Socialization and education were conducted to provide partners with an understanding of the agrivoltaic concept, which integrates agricultural production and renewable energy. Results showed a significant increase in partners' understanding of this technology. The selection of land for solar panel installation was based on stable sun exposure, so that the panels can function optimally without disrupting agricultural activities. The technology transfer process involved the installation of solar panels, the construction of greenhouses, and the application of supporting technologies such as sensor-based automatic irrigation systems. This technology has increased the efficiency of water and energy use, and created more stable farming conditions. Overall, the program succeeded in supporting energy security and agricultural productivity in peatlands, as well as having a positive impact on the welfare of farmers and environmental sustainability.